Rethinking comparative studies: an agent-centred perspective - Clark, G; Tracey, P; Smith, H (Blackwell Publishing, 2002)
Broadly speaking, three rival approaches to comparative research can be identified. One suggests that the study of different countries and their regions is unproblematic, and is best exemplified by scholarship in mainstream (particularly neoclassical) economics. Stress is placed on an integrated theoretical perspective emphasizing apparent similarities while explaining differences by reference to the heritage of nations and places. By way of a contrast a second approach, which owes much to anthropology, relies on case studies and presumes the existence of profound differences between countries and regions. Stress is placed upon the local cultural, social and political factors that sustain persistent difference. A third approach is rooted in new institutional economics and argues for the significance of national institutional frameworks, supposing that those frameworks shape and structure the actions of agents. Whatever their differences and origins, idealism drives each method of comparative study. In this article, we consider these rival theories of comparative study, and suggest an alternative model based upon a set of fundamental assumptions about the nature of human cognition. These assumptions are the building blocks for our analysis, which has global applicability. We focus in particular upon consciousness and reflexivity, the interplay between agency and structure, and the practice of comparative studies. In the penultimate section of the article we comment on the limits of comparative studies emphasizing the problems that lie behind the translation of complex concepts within and between languages.